Diagnosis and Management of Severe Peripartum Cardiomyopathy: Diagnosis dan Manajemen Kardiomiopati Peripartum Berat - Sidhi Laksono; Ananta S. Prawara; Reynaldo Halomoan (Indonesian Journal of Obstetrics and Gynecology, 2021)
Objective: To describe the diagnosis and management of severe peripartum cardiomyopathyMethods: A case report.Case: A 35-year-old woman presented with dyspnea and leg edema. The patient gave birth 3 months ago. The hemodynamic was unstable and the physical examination showed a mild rhonchi in the basal of the lung and pansystolic murmur in the apex. Echocardiography showed a dilated heart chamber and reduced ejection fraction (30%). The patient was diagnosed as severe PPCM. The initial management was to stabilize the patient using furosemide, catecholamine, and vasopressor administration. After the patient’s condition was stable, ramipril, bisoprolol, and bromocriptine were given as heart failure therapy.Conclusions: Patient with suspicion of PPCM should be managed thoroughly from detailed history taking to proper diagnostic testing such as echocardiography. Prompt treatment of severe PPCM according to the guideline will improve the cardiac function.Key words: catecholamines, echocardiography, peripartum cardiomyopathy, pregnancy, vasopressor. Abstrak Tujuan: Untuk mendeskripsikan mengenai diagnosis dan manajemen pasien pada kasus kardiomiopati peripartum yang berat.Metode: Laporan kasus.Kasus: Seorang Perempuan 35 tahun datang dengan dispnea dan edema tungkai. Pasien melahirkan 3 bulan lalu. Hemodinamik tidak stabil dan pemeriksaan fisik menunjukkan ronki ringan di basal paru dan murmur pansistolik di apeks. Ekokardiografi menunjukkan dilatasi ruang jantung dan fraksi ejeksi berkurang (30%). Pasien didiagnosis dengan PPCM berat. Penatalaksanaan awal adalah menstabilkan pasien dengan pemberian furosemid, katekolamin, dan vasopresor. Setelah kondisi pasien stabil, diberikan ramipril, bisoprolol, dan bromokriptin sebagai terapi gagal jantung.Kesimpulan: Pasien dengan kecurigaan PPCM harus dikelola secara menyeluruh mulai dari anamnesa yang rinci hingga uji diagnostik yang tepat seperti ekokardiografi. Pengobatan segera untuk PPCM derajat berat yang sesuai dengan pedoman akan meningkatkan fungsi jantung.Kata kunci: ekokardiografi, kardiomiopati peripartum, katekolamin, kehamilan, vasopressor.